ENHANCING CURRICULUM RELEVANCE IN VOCATIONAL HOSPITALITY EDUCATION: A COMMUNITY ENGAGEMENT EXPERIENCE AT SMK NEGERI 3, BOGOR CITY - Yuwantiningrum, Sri Endah; Rainanto, Bambang Hengky; Utami, Nisa Rahmaniyah; Sukma, Braja Eka (LPPM Univ. Ibn Khaldun Bogor, 2025)
This community engagement initiative addresses the need for curriculum enhancement in the Hospitality Department of SMK Negeri 3, a vocational school focused on producing industry- ready graduates. The initiative was conducted through a structured collaboration involving the review and revision of hospitality-related subjects to align with the Indonesian National Work Competency Standards (Standar Kompetensi Kerja Nasional Indonesia/SKKNI) for Hotel Services. The SKKNI outlines key units of competency required in the hospitality sector, including handling guest check-in and check-out procedures, managing reservations, maintaining cleanliness and order in housekeeping, and delivering food and beverage services. The methodology included curriculum gap analysis, document review, focused group discussions with vocational teachers, and systematic curriculum redesign. Key revisions introduced industry-based learning outcomes, performance-based assessments, contextual case studies, and integrated soft skills development. The engagement not only improved curriculum alignment with national standards but also enhanced teacher capacity and student readiness for the labor market. Feedback from stakeholders indicated a strong potential for implementation and scalability across other vocational institutions. This activity exemplifies the value of academic involvement in vocational education reform and highlights the importance of continuous curriculum adaptation to industry trends. The paper presents the process, outcomes, and strategic value of such initiatives in strengthening vocational education, in line with national human resource development priorities.